Hyperspaces of arcs containing a point - Chacón-Tirado, Mauricio; López, María de J.; Suárez-López, José Luis (Topology Proceedings, 2023)
For a metric continuum X and for p X, we define the hyperspace Arcs(p, X) as the set of all arcs in X that contain the point p, endowed with the Hausdorff metric. We show geometric models of Arcs(p, X), in the case when X is the arc, the simple closed curve, the simple triod, the noose and the (1x)-continuum. Moreover, we present a characterization of dendrites in terms of this hyperspace.